Study on coordinated allocation of conventional and unconventional water resources in typical regions of North China - Chai, Qihui; Han, Wenhao; Wan, Fang; Ding, Zelin; Wu, Feng (Frontiers in Earth Science, 2023)
Introduction: The North China Plain is an important production base of grain, cotton, and fruits in China. However, the climate is dry and rainless, and thus, water resources are scarce. The combination of water resources, population, and cultivated land is extremely unbalanced, making the region a serious water shortage area in China. In addition to long-term groundwater over-exploitation, water shortage has become an important bottleneck, restricting the economic and social development of the North China Plain and national food security. Therefore, making full use of unconventional water resources and reducing the proportion of conventional water resources will alleviate the shortage of water resources and improve the utilization of water resources. Methods: Taking Hengshui City as an example, this paper establishes an optimal allocation model of water resources with the minimum relative water shortage rate as the objective function, the coordinated allocation of water resources between conventional and unconventional water resources is studied, and various available water sources are effectively allocated between regions and water use departments. The genetic algorithm is used to study the model, by taking 2020 as the starting year, and optimize the allocation of water resources in Hengshui City between 2020 and 2025. Results and Discussion: The results show that the water demand of each county in Hengshui City will be guaranteed in 2025, and there will be no water shortage. In the 2025 level year, the total amount of unconventional water resources in Hengshui City will increase compared with that in 2020, with an increase of 21.9144 million m3. Among them, there will be an increase in brackish water consumption, 11.3244 million m3, and an increase in sewage reuse water consumption, 10.59 million m3, which will effectively alleviate the contradiction between supply and demand of water resources in Hengshui City.